YIELD PERFORMANCE AND ECONOMICS OF CLUSTER BEAN AS INFLUENCED BY WEED CONTROL MEASURES UNDER RAINFED CONDITIONS - C. RADHA KUMARI* and B. SAHADEVA REDDY, (The Journal of Research ANGRAU, 2021)
The field experiment was conducted to find out the effect of weed management practices onyield performance and economy of clusterbean (Cyamopsis tetragonoloba) under rainfed conditionsduring rainy season of Kharif, 2015-16.The results revealed that weed density, dry weight and weedcontrol efficiency were not significantly (p >0.05) influenced by different weed management practices.The lowest weed density, dry weight and highest weed control efficiency were recorded with handweeding twice at 20 DAS and 40 days after sowing (DAS) (weed-free check) although the result is notsignificant. However,seed yield varied significantly due to different weed management practices. Thehighest seed yield (477 kg ha-1) was obtained with hand weeding twice at 20 DAS and 40 DAS whichwas on par with post-emergence (POST) of imazethapyrat 40 g a.i ha-1 at 20 DAS (465 kg ha-1), preemergence(PRE) application of pendimethalin at 0.75 kg a.i ha-1+ imazethapyrPOST at 40 g a.iha-1 at 20 DAS (437 kg ha-1) and pendimethalin PRE @ 0.75 kg a.i ha-1+ quizalofopethyl POST @37.5 g a.iha-1 at 20 DAS (411 kg ha-1). The higher gross (Rs. 14296 ha-1) and net returns (Rs. 9196ha-1) were obtained with hand weeding twice at 20 DAS and 40 DAS followed by imazethapyr POST @40 g a.i ha-1 at 20 DAS. The highest benefit-cost ratio was registered with hand weeding at 20 DAS(0.69) followed by weedy check (0.62) and hand weeding twice at 20 DASand 40 DAS (0.60).